The Modified Alternate Healthy Eating Index-2010 and Breast Cancer Risk among Women from Karachi, Pakistan - Uzma Shamsi; Tiffany Gill; Shaista Khan; Iqbal Azam; David Callen; Romaina Iqbal (Journal of the Pakistan Medical Association, 2022)
Objective: To determine any relationship of diet with breast cancer risk. Methods: The case-control study was conducted at Aga Khan University Hospital and the Karachi Institute of Radiation and Nuclear Medicine, Karachi, from February 2015 to July 2017, and comprised cases with a confirmed diagnosis of breast cancer and controls. Data was collected using the Alternate Healthy Eating Index 2010, which was modified according to the particular cultural patterns of diet in the Pakistani population. Data was analysed using SPSS 21. Results: Of the 1124 subjects, 374(33.3%) were cases and 750(66.7%) were controls. High intake of grains, both whole and refined including white rice, was associated with breast cancer (odds ratio: 2.53; 95% confidence interval: 1.69-3.79; p<0.001). There was no association of breast cancer with Alternate Healthy Eating Index 2010 score (odds ratio: 1.85; 95% confidence interval: 0.61-1.17; p=0.291). Conclusions: There was found a need for awareness of a healthy diet based on more of whole grains and brown rice replacement with refined grains and white rice, respectively. Key Words: Diet, AHEI-2010, Grains, Breast cancer.